Analiza „Sprawiedliwości” - Maj, Karolina (Kwartalnik Prawa Publicznego, 2016)
Defining the notion of “justice” has been a key goal of researches in the fields of philosophy, ethics, law, psychology and many others for thousands of years. The article presents the various definitions of justice, from the historical perspective of the issue to the contemporary understanding of justice. This concept is defined in terms of human morality, just state and fair law. However, the challenge is to define the existence of the definition of “justice”, or whether there is one, what the author presents considering about the essence of justice.